2015
DOI: 10.4314/ajtcam.v12i2.9
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxymethyl furfural in chinese herbal medicines: Its formation, presence, metabolism, bioactivities and implications

Abstract: Background: Chinese herbal medicines (CHMs) must be processed before being prescribed to patients. During the processing, some CHMs became brown and as such 5-hydroxymethyl furfural (HMF) generated. Increasing attention is being paid to the safety and effectiveness of HMF. Methods: This paper summarized previous and recent reports on HMF formation, its presence in CHMs, its metabolism and bioactivities, together with its implications for CHMs. Results: HMF had been detected in 41 CHMs, and increased by about 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 47 publications
(50 reference statements)
0
3
0
Order By: Relevance
“…The DDMP and HMF were also identified as main bitter compounds in hydrophobic fraction of whole wheat bread 22 . Many Chinese medicines with strong bitter‐taste have been found to contain HMF and DDMP, 32,33 further suggesting their bitter attribution.…”
Section: Resultsmentioning
confidence: 97%
“…The DDMP and HMF were also identified as main bitter compounds in hydrophobic fraction of whole wheat bread 22 . Many Chinese medicines with strong bitter‐taste have been found to contain HMF and DDMP, 32,33 further suggesting their bitter attribution.…”
Section: Resultsmentioning
confidence: 97%
“…1s and 2s (Gao et al, 2015;Guo et al, 2012;Liu and Wen, 2013). We have previously demonstrated that, during the steam processing of SRR, the Maillard reaction takes place, which is a complex chemical reaction between amino acids and reducing sugars and finally forms melanoidins after a series of changes including rearrangement, enolization, degradation, polymerization and condensation (Guo et al, 2012).…”
Section: Tbars and Gsh Concentrations In Jejunum Mucosamentioning
confidence: 96%
“…In view of the aforesaid, 5-hydroxymethylfurfural (5-HMF) and its derivatives (2,5-diformylfuran, dimethyl furfural, γ-valerolactone, levulinic acid, etc. ), which can be obtained by transformation of biomass-derived sugars in IL media, are among the particularly promising building blocks. These biomass-derived products are proposed to be used in fine chemical synthesis of polymers, fuels, smart organic materials, and pharmaceuticals. 5-HMF is abundant in sugar-containing processed foods and drinks, such as honey, coffee, juice, beverages, dried fruits, and bakery products. , Recent studies have revealed numerous beneficial biological activities of 5-HMF; it has entered clinical studies as an anti-sickling agent. In particular, various aminoalkylhydroxymethylfuran derivatives produced from furfural-based molecules are key structural units in many biologically active natural and artificial products involved in various pharmaceutical activities (as diuretics, anticancer, antihypertensive, or antimuscarinic agents). …”
Section: Introductionmentioning
confidence: 99%